Talking to students: a proposal for pedagogical action (Revista INTEREDU11, 2024)
Teachers have an important role, because there are teachings that go beyond the presentation of knowledge and connect with a way of being and being in life. The objective of this educational initiative focused on systematizing the implementation of a strategy to promote teacher-student communication in higher education. Methodology: The proposal is ascribed to the principles of the interpretative paradigm, concretized in an introspective-experiential approach. The technique for data collection consisted of an unstructured interview, applied to 21 volunteer students of the Teacher Training Degree in Primary Education, belonging to the Faculty of Education of the María Zambrano Campus in Segovia (Spain). Results: It was observed that participation in the educational experience was a positive experience for the students and favored the classroom environment, stimulating active participation in the classes and contributing to a higher attendance to the subject throughout the academic year of those students who participated in the interview. In addition, the dedication of the teacher was positively highlighted. Conclusion: The educational proposal was well received by the students and had a positive impact on the classroom climate and on the development of the teaching-learning process.
Keywords: Education; University course; Communication; affectivity; teaching